Water-level fluctuations are key for phytoplankton taxonomic communities and functional groups in Poyang Lake. (September 2019) - Liu, Jinfu; Chen, Yuwei; Li, Mingjia; Liu, Baogui; Liu, Xia; Wu, Zhaoshi; Cai, Yongjiu; Xu, Jinying; Wang, Jianjun
Highlights: Water-level positively correlated with cyanobacteria and negatively with diatom. Water-level directly and indirectly affected phytoplankton assemblages. Functional groups were more sensitive to water-level than taxonomic communities. Abstract: Biological species can be assembled into functional groups based on functional traits, which are keys to understanding the response of phytoplankton to environmental factors, such as the physical and chemical characteristics of aquatic systems. Here, we studied the taxonomic and functional communities of phytoplankton over three years in Poyang Lake and further examined the effect of water-level on these groups. Phytoplankton were generally dominated by diatoms across seasons, followed by cyanobacteria and green algae. Functional groups were mainly composed of organisms tolerant to fluctuating mixing intensities, such as groupP, which was mainly composed of filamentous Aulacoseira granulata and showed a typical seasonal variation. Compared to the other physical and chemical variables of the lake, water-level showed a greater influence on seasonal variations in phytoplankton total biomass, taxonomic communities and functional groups. The influence of water-level on phytoplankton communities included two aspects: direct effects of biomass dilution and mixing and indirect effects of nutrient dilution and underwater light availability. Our results also indicated that the functional groups were more sensitive to water-level than the taxonomic communities, which was supported by the higher variation of functional groups explained solely by water-level. Collectively, these findings illustrate the direct and indirect effects of water-level on phytoplankton taxonomic communities and functional groups, and providing insights into how water-level can alter phytoplankton communities in a larger complex floodplain system.